Psychological portrait of the 20th century humanist philosopher Wladyslaw Tatarkiewicz - Ilyina, Yulia A. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article deals with the history of formation of philosophical personality of Polish thinker of 20th century W. Tatarkiewicz with regard to all concomitant circumstances of being and scientific nature. In order to create the most complete picture and multifaceted image of W. Tatarkiewicz, the attention is focused on the works of some Polish researchers of his life and work T. Rzepa, J. Jadacki and J. Woleński. On the basis of reproduction of autobiography of W. Tatarkiewicz his contribution to the world of philosophy and cultural processes is noted.